Plea bargaining and the trial penalty in Canada. (2015) - Alati, Daniel
This article takes an in-depth look into sentencing and into a concept that seems to be inherent within it, that is, the trial penalty. It seeks to answer the question "Should there be a trial penalty?". In doing so, it begins by analysing the pros and cons of plea bargaining and argues that the weight of the disadvantages of the process, taken together with the need to respect entrenched constitutional rights regarding the presumption of innocence and the right to a fair trial, mean that a trial penalty should not exist. It is then argued that while the intuitive existence of an explicit trial penalty is accepted by many within the system, there is a lack of empirical evidence to prove said existence. The article concludes by offering possible solutions to various problems associated with the plea process, as it is currently practised.